Forty-one recent cases of invasive zygomycosis from a global clinical registry - Vehreschild, Maria J. G. T.; Heinz, W. J.; Kindo, A. J.; Rickerts, V.; Lass-Flörl, C.; Beisel, C.; Herbrecht, R.; Roth, Y.; Silling, G.; Ullmann, A. J.; Borchert, K.; Egerer, Gerlinde; et al. (The journal of antimicrobial chemotherapy, 2010)
Invasive zygomycosis accounts for a significant proportion of all invasive fungal diseases (IFD), but clinical data on the clinical course and treatment response are limited.Fungiscope™—A Global Rare Fungal Infection Registry is an international university-based case registry that collects data of patients with rare IFD, using a web-based electronic case form at www.fungiscope.net.Forty-one patients with invasive zygomycosis from central Europe and Asia were registered. The most common underlying conditions were malignancies (n=26; 63.4%), diabetes mellitus (n=7; 17.1%) and solid organ transplantation (n=4; 9.8%). Diagnosis was made by culture in 28 patients (68.3%) and by histology in 26 patients (63.4%). The main sites of infection were the lungs (n=24; 58.5%), soft tissues (n=8; 19.5%), rhino-sinu-orbital region (n=8; 19.5%) and brain (n=6; 14.6%). Disseminated infection of more than one non-contiguous site was seen in six patients (14.6%). Mycocladus corymbifer was the most frequently identified species (n=10, 24.4%). A favourable response was observed in 23 patients (56.1%). Overall survival was 51.2% (n=21). At diagnosis, four patients (9.8%) were on continuous antifungal prophylaxis with itraconazole (n=1; 2.4%) or posaconazole (n=3; 7.3%). Initial targeted treatment with activity against zygomycetes was administered to 34 patients (82.9%). Liposomal amphotericin B was associated with improved response (P=0.012) and survival rates (P=0.004).Pathogen distribution and, consequently, drug susceptibility seem to vary across different geographic regions. Furthermore, protection from invasive zygomycosis for patients on posaconazole prophylaxis is not absolute. Our findings indicate that the use of liposomal amphotericin B as first-line treatment for patients diagnosed with zygomycoses merits further investigation, preferably in the form of a clinical trial.
Erstmals am 11 December 2009 online veröffentlicht
Gesehen am 22.06.2023